2020
DOI: 10.1186/s12937-020-00545-9
|View full text |Cite
|
Sign up to set email alerts
|

Are dietary intake and nutritional status influenced by gender? The pattern of dietary intake in Lao PDR: a developing country

Abstract: Background: Recognition of discrepancies between men and women in nutritional intake is important to tackle food and nutrition insecurity and the often-double burden of malnutrition. The purpose of this study was to assess nutritional status and dietary intake of the Lao population, with a focus on possible influences of gender.Methods: Dietary intake was assessed in a national cross-sectional study of 1771 randomized participants aged from 1.01 to 89 years, using 24-h dietary recall. Dietary reference intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
2
12
0
2
Order By: Relevance
“…Insufficient intake of dairy products and fruit can cause insufficient intake of Ca and micronutrients, and contribute to the inadequate nutrition levels of developing countries ( Allen, 2003 ; Díaz et al, 2003 ; Ramakrishnan, 2003; Müller and Krawinkel, 2005 ). Consistent with our results, a recent study using INMUCAL on the nutritional status of individuals of all ages in Laos revealed that vitamin A, vitamin B, vitamin C, and micronutrients, including Ca and Fe, are inadequately ingested ( Ratsavong et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Insufficient intake of dairy products and fruit can cause insufficient intake of Ca and micronutrients, and contribute to the inadequate nutrition levels of developing countries ( Allen, 2003 ; Díaz et al, 2003 ; Ramakrishnan, 2003; Müller and Krawinkel, 2005 ). Consistent with our results, a recent study using INMUCAL on the nutritional status of individuals of all ages in Laos revealed that vitamin A, vitamin B, vitamin C, and micronutrients, including Ca and Fe, are inadequately ingested ( Ratsavong et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…While food insecurity is assumed to be a major determinant of malnutrition in Lao PDR, analysis by The World Bank demonstrated that insufficiently diverse diets are of greater concern than meeting caloric intake (Osornprasop & Pimhidzai, 2016 ). In a nationally representative food consumption survey, >80% of pregnant and lactating women were estimated to have insufficient intakes of vitamin A, thiamine, riboflavin, niacin and calcium (Ratsavong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, men need more nutrients than women. 20 This study used respondents in the age range of 18-25 years which was included in the category of late teens. Based on previous research, young adults or adolescents were known to be at risk for vitamin D deficiency which was influenced by habits such as consuming vitamin D below the recommended limit per day and lack of outdoor physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Research has shown that an increase in BMI was associated with lower levels of 25-hydroxyvitamin D (25D), the active form of vitamin D in the body. [19][20][21] The mechanism of vitamin D deficiency in obese patients included high-fat accumulation resulting in a decrease in the bioavailability of vitamin D in the body due to the fat-soluble nature of vitamin D, causing a reduction in the release of vitamin D from fat into the systemic circulation. 22,23 There are two pathways for vitamin D intake: the first comes from food and beverages consumed.…”
Section: Discussionmentioning
confidence: 99%